Precautionary saving intention in sspn by Malaysian parents: theory of planned behaviour approach - Musa, Rosidah; Putit, Lennora; Hamzah, Haznan (2011)
The paper investigated the direction and magnitude of the underlying variables that influence parents' intention to save in the National Education Saving Scheme (SSPN). The scheme was formed in 2004 by the government to encourage parents to save for their children's tertiary education and to rely less on education loans. The scheme was also created as there were numerous reports of defaulted payment by former students on their education loan and forcing the lending financial institutions to take legal action and subsequently declaring some for the defaulters bankrupt. Permission was first obtained from the Ministry of Education, Jabatan Pelajaran Selangor and Jabatan Pelajaran Wilayah Persekutuan Kuala Lumpur. The chosen schools were national type primary schools and were picked randomly based on their location. A total of 1000 questionnaires were distributed to 10 schools in various locations within the Selangor's state border and also Wilayah Persekutuan Kuala Lumpur. 796 questionnaires were returned and after cleansing, 561 questionnaires were usable. A total of 63 questions were asked and using a combination of 7 point Likert's Scale and categorical scale, the researchers was able to determine the direction, magnitude and the relationships of the proposed latent variables. Measurement items were obtained from reviews of literatures and from pilot study conducted prior to the proper research. The model proposed are significant at p<0.05 and from multiple regression analysis, the independent variable of Parents Aspiration seem to be the main contributor to the variance in the dependent variable of Attitude towards Saving. Further, there are statistically significantly different in term of Intention to save between respondents in the town and suburban area at p=O.4 but no significant different between father and mother in term of intention to save in SSPN.